Youth, participation, and power spaces in organizations in Metropolitan Lima. Approaches to the Bicentennial - Evans Morales, Franco (2020)
The article considers young people as strategic actors for development that move between logics of emancipation and subordinate integration, therefore, youth is reconstructed as an unequal and differentiated condition whose social positions are sustained in power relations with the world adult-centric that impact on the dynamics of organized youth participation. For this purpose, through interviews, the aim is to understand young people and their meanings of organized participation, analyze the forms of relationship between organized young people and political authorities and reflect on the institutionalized spaces of youth participation. It is rescued that young people define themselves and define others as youthful subjects according to the system of power relations in which they are inserted, that participation is a resource to generate changes in the environment and that there are institutional barriers to the relationship with authorities.